Comparison of clinical and environmental isolates of Acanthamoeba based on morphology, protease and gelatinase activity, and the cysteine proteinase gene - Penuliar, Gil M.; Matias, Ronald R.; Natividad, Filipinas F. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 22 No 1 (2010), 2011)
Acanthamoeba spp. are opportunistic pathogens that cause amebic keratitis and granulomatous amebic encephalitis in man. Recent attempts to correlate pathogenicity with species have been proven difficult due to inconsistencies in morphology-based classification. The objectives of this study were: (1) to compare clinical and environmental isolates based on morphology, protease and gelatinase activity, and the cysteine proteinase (CP) gene, and (2) to determine whether these features can be used to differentiate the isolates. Results show some degree of variation in trophozoite and cyst morphology. Zymography, demonstrated gross differences in banding patterns, and the protease activity of clinical isolates was greater than the environmental isolates (p-value < 0.01).  Amplification of the CP gene yielded two bands in the environmental isolates, approximately 755 bp and 440 bp in length. In contrast, only one band, either the 755 bp or 440 bp band was amplified in the clinical isolates. The results confirmed the limitations of morphology in differentiating Acanthamoeba species, and suggest that zymography, protease activity, and detection of the CP gene are useful reference tests to distinguish pathogenic from non-pathogenic isolates.
Keywords: Acanthamoeba; protease activity; cysteine proteinase gene